Role of the IGF-1 Axis in Overcoming Resistance in Breast Cancer - Ianza, Anna; Sirico, Marianna; Bernocchi, Ottavia; Generali, Daniele (Frontiers in Cell and Developmental Biology, 2021)
Over the last two decades many studies have demonstrated that the insulin-like growth factor-1 (IGF-1) is involved in a number of patho-physiological processes, as well as in the development of different types of solid tumors, including breast cancer. Preclinical and clinical data showed that IGF-1 receptor (R) is overexpressed and hyper-phosphorylated in several subtypes of breast cancer. The central implications of this pathway in tumor cell proliferation and metastasis makes it an important therapeutic target. Moreover, the IGF-1 axis has shown strong interconnection with estrogen regulation and endocrine therapy, suggesting a possible solution to anti-estrogen resistance. IGF-1R might also interfere with other pivotal therapeutic strategies, such as anti HER2 treatments and mTOR inhibitors; several clinical trials are ongoing evaluating the role IGF-1R inhibition in modulating resistance mechanisms to target therapies. Our aim is to offer an overview of the most recent and significant field of application of IGF-1 inhibitors and relevant therapeutic strategies, weighing their possible future impact on clinical practice.